A Review Study on the Biomedical Potentials of Seaweeds Specie - Femi-Adepoju, Abiola Grace; Adepoju, Adeyinka Olufemi; Fadiji, Ayomide Emmanuel; Peters, Jonathan Jergbo (Pharmacognosy Reviews)
Seaweeds have long been used in Asian nations as food and medicine due to their abundance of bioactive compounds that can treat diseases like cancer, inflammation, oxidative stress, allergies, diabetes, thrombosis, obesity, and hypertension. Algae extracts have been found to improve the activity of killer cells through various processes, including activation of the non-specific immune system, inhibition of cell growth, and induction of terminal differentiation and apoptosis. Endothelial cells exhibit greater sensitivity to inhibitors in cytotoxic and biomedical research due to their rapid genetic stability and high rate of proliferation. Compounds obtained from natural products have potential as anti-angiogenic, antioxidative, and anti-microbial agents due to their promising activities in overcoming the adverse effects posed by synthetic drugs on human health. Seaweed extracts contain various secondary metabolites, including polysaccharides, lipids, fatty acids, sterols, phenolic compounds, carotenoids, lectins, alkaloids, and terpenes, making them potential therapeutic agents largely screened for the development of antimicrobial drugs. Antioxidants are essential for health, with numerous health benefits including anti-aging and anti-inflammatory properties. Research is rapidly progressing to understand the antioxidant properties of natural foods, including seaweeds. Seaweed extracts have shown dose-dependent free radical scavenging effects, inhibiting lipid peroxidation and glutathione-S-transferase activities. Polysaccharides isolated from various seaweed species have shown anti-proliferative effects on human leukemia and Ca9-22 oral cancer cell lines. Marine algae are rich in antioxidants and have potential applications in pre-clinical research for drug development, treating various ailments and as food preservatives. Further investigation is required to determine the most effective agents.
Keywords: Biomedical; Seaweed; Disease; Anti-microbial; Anti-cancer